(untitled) (Pulse, 2023)
Corona virus causes severe contagious acute respiratory syndrome known as coronavirus disease 2019 (COVID-19). Several initiatives have been taken to tackle so far. One of them, being therapy based biological nano particles “Exosomes”. Administration of exosomes loaded with immunomodulatory cargo in combination with antiviral drugs will be a promising approach. This study deals with the exosomal isolation techniques of the Bruton Tyrosine Kinase (BTK) protein from cells. It represents initial trials to establish a method to isolate exosomes from human B cells. Pulse Volume 12-14 2020-2022 p.22-25